“Es el amor un ratoncito”: Una aproximación a la tonadilla en el Perú del siglo XVIII (un género musical rebelde al ideal ilustrado) - Torres Arancivia, Eduardo (Notas de Antropología de las Américas, 2023)
In Peruvian´s music history, the Tonadilla, as a musical genre, has not been approached with the required Depth. The Tonadilla is an orchestrated song with a humorous theme waswidely used in theatrical plays in Spain and Latin America between 1750 and 1820 and wich enjoyed a wide popularity. This article will address the subversive carácter of the Tonadilla at a technical-musical level (the use of musical modernity at service of vulgarity) and in its licentious themes. Likewise, this subversión will be understood mainly as directed against the Enlightened ideal of aesthetic beauty and even civilization, an ideal that an intelletual elite tried to impose – without much success- in the court of Lima at that time.